Effects of Sodium Restriction on Activation of the Renin-Angiotensin-Aldosterone System and Immune Indices During HIV Infection. (22nd August 2016) - Srinivasa, Suman; Burdo, Tricia H.; Williams, Kenneth C.; Mitten, Emilie K.; Wong, Kimberly; Fitch, Kathleen V.; Stanley, Takara; Adler, Gail K.; Grinspoon, Steven K.
Abstract: Background. Human immunodeficiency virus (HIV)–infected patients demonstrate increased activation of the renin-angiotensin-aldosterone system (RAAS). We evaluated changes in immune markers with physiological RAAS activation. Methods. Immune activation markers were assessed serially in 18 HIV-infected and 7 non–HIV-infected subjects consuming an ad libitum diet followed by a standardized low-sodium diet. Results. Levels of CCL-2 ( P = .0004) and soluble CD163 ( P = .0001) significantly increased with sodium restriction and RAAS activation, compared with levels in individuals with ad libitum sodium intake, among chronically treated HIV-infected subjects (mean duration of ART [±SEM], 11 ± 1 years), but not among non–HIV-infected subjects of similar age and sex. Conclusions. Dietary sodium restriction, which activates RAAS, uniquely stimulates critical indices of immune activation during HIV infection. Clinical Trials Registration. NCT01407237.